Genetic testing in children enrolled in epilepsy surgery program. A real-life study - Straka, Barbora; Splitkova, Barbora; Vlckova, Marketa; Tesner, Pavel; Rezacova, Hana; Krskova, Lenka; Koblizek, Miroslav; Kyncl, Martin; Maulisova, Alice; Bukacova, Katerina; Uhrova-Meszarosova, Anna; Musilova, Alena; et al. (European journal of paediatric neurology, 2023)
OBJECTIVE: Although genetic causes of drug-resistant focal epilepsy and selected focal malformations of cortical development (MCD) have been described, a limited number of studies comprehensively analysed genetic diagnoses in patients undergoing pre-surgical evaluation, their outcomes and the effect of genetic diagnosis on surgical strategy. METHODS: We analysed a prospective cohort of children enrolled in epilepsy surgery program over January 2018-July 2022. The majority of patients underwent germline and/or somatic genetic testing. We searched for predictors of surgical outcome and positive result of germline genetic testing. RESULTS: Ninety-five patients were enrolled in epilepsy surgery program and 64 underwent resective epilepsy surgery. We ascertained germline genetic diagnosis in 13/74 patients having underwent germline gene testing (pathogenic or likely pathogenic variants in CHRNA4, NPRL3, DEPDC5, FGF12, GRIA2, SZT2, STXBP1) and identified three copy number variants. Thirty-five patients underwent somatic gene testing; we detected 10 pathogenic or likely pathogenic variants in genes SLC35A2, PTEN, MTOR, DEPDC5, NPRL3. Germline genetic diagnosis was significantly associated with the diagnosis of focal epilepsy with unknown seizure onset. SIGNIFICANCE: Germline and somatic gene testing can ascertain a definite genetic diagnosis in a significant subgroup of patients in epilepsy surgery programs. Diagnosis of focal genetic epilepsy may tip the scales against the decision to proceed with invasive EEG study or surgical resection; however, selected patients with genetic focal epilepsies associated with MCD may benefit from resective epilepsy surgery and therefore, a genetic diagnosis does not disqualify patients from presurgical evaluation and epilepsy surgery.
Keywords: genetické testování; Epilepsy; epilepsie; Epilepsies, Partial; Drug Resistant Epilepsy; Prospective Studies; dítě; Nerve Tissue Proteins; mTOR; Malformations of Cortical Development; epilepsie parciální; Child; Genetic testing; proteiny aktivující GTPasu; Malformations of cortical development; Humans; prospektivní studie; GTPase-Activating Proteins; malformace mozkové kůry; proteiny nervové tkáně; fibroblastové růstové faktory; Fibroblast Growth Factors; Paediatric epilepsy surgery; Focal drug-resistant epilepsy; Genetic Testing; refrakterní epilepsie; lidé